2012
DOI: 10.1073/pnas.1201271109
|View full text |Cite
|
Sign up to set email alerts
|

Wave-particle dualism and complementarity unraveled by a different mode

Abstract: The precise knowledge of one of two complementary experimental outcomes prevents us from obtaining complete information about the other one. This formulation of Niels Bohr's principle of complementarity when applied to the paradigm of wave-particle dualism-that is, to Young's double-slit experiment-implies that the information about the slit through which a quantum particle has passed erases interference. In the present paper we report a double-slit experiment using two photons created by spontaneous parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 29 publications
5
68
0
Order By: Relevance
“…There is equivocation in two places (p. 9314 and p. 9316) about the use of mechanical slits in Menzel et al [10]. On p. 9314, their abstract creates an ambiguity as to whether mechanical slits were actually used when they say, "According to quantum field theory the signal photon is then in a coherent superposition of two distinct wave vectors giving rise to interference fringes analogous to two mechanical slits."…”
Section: Presence or Absence Of Mechanical Slitsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is equivocation in two places (p. 9314 and p. 9316) about the use of mechanical slits in Menzel et al [10]. On p. 9314, their abstract creates an ambiguity as to whether mechanical slits were actually used when they say, "According to quantum field theory the signal photon is then in a coherent superposition of two distinct wave vectors giving rise to interference fringes analogous to two mechanical slits."…”
Section: Presence or Absence Of Mechanical Slitsmentioning
confidence: 99%
“…In 2012 Menzel et al [10] reported that they had successfully conducted a Young's two slit experiment in which they had located which slit a photon passed through, and contrary to Bohr's complementarity principle still obtained an interference pattern.…”
Section: Menzel Et Al Experimentsmentioning
confidence: 99%
See 3 more Smart Citations